The effect of the substrate potential during deposition on the structure and properties of the binanolayer multiperiod composites (TiAlSi)N/MeN (Me – Zr, Nb, Cr, Mo) - Sobol’, O.V.; Andreev, A.A.; Mygushchenko, R.P.; Stolbovoy, V.A.; Postelnуk, A.A.; Meylekhov, A.A.; Dolomanov, A.V.; Rebrova, Ye.M. (Вопросы атомной науки и техники, 2018)
It is proposed to use the multiperiod binanolayer composites (TiAlSi)N/MeN (Me-Zr, Nb, Cr, Mo) for controlling the structure, stress state and mechanical properties of a multi-element nitride (TiAlSi)N. The deposition of the layers was carried out by the method of vacuum-arc evaporation at different bias potentials on the substrate Uₕ = -110 and -200 V. It has been determined that mononitrides with a high Me-N binding energy in the binanolayer composite determine the crystallite growth in thin (nanometer) layers. The growth texture is formed in composites containing mononitrides based on transition metals with a relatively small atomic mass (Cr, Mo) at Uₕ = -110 V. The growth texture is formed at a larger Ub = -200 V when dealing with mononitride based on heavy metal (Zr). The greatest hardness is achieved in textured materials deposited at Uₕ = -200 V. This is typical both for a monolayer multi-element nitride (TiAlSi)N (hardness is 42.5 GPa) and for multiperiod nanolayer composites based on it (the highest hardness is 47.9 GPa for a composite (TiAlSi)N/ZrN). Запропоновано використовувати багатоперіодні бінаношарові композити систем (TiAlSi)N/MeN (Me – Zr, Nb, Cr, Mo) для управління структурою, напруженим станом і механічними властивостями багатоелементного нітриду (TiAlSi)N. Осадження шарів здійснювалося методом вакуумно-дугового випаровування при різних потенціалах зміщення на підкладці Uₕ = -110 і -200 В. Встановлено, що в бінаношаровому композиті мононітриди з великою енергією зв'язку Me–N задають переважну орієнтацію росту кристалітів у тонких (нанометрових) шарах. При Uₕ = -110 В текстура зростання формується в композитах, які містять мононітриди на основі перехідних металів з відносно невеликою атомною масою (Cr, Mo). У разі мононітриду на основі важкого металу (Zr) текстура утворюється при більшому Uₕ = -200 В. Найбільша твердість досягається в текстурованих матеріалах, осаджених при Uₕ = -200 В. Це характерно, як для моношарового багатоелементного нітриду (TiAlSi)N (досягнута твердість 42,5 ГПа), так і для багатоперіодних наношарових композитів на його основі (найбільша твердість 47,9 ГПа отримана для композиту (TiAlSi)N/ZrN). Предложено использовать многопериодные бинанослойные композиты систем (TiAlSi)N/MeN (Me – Zr, Nb, Cr, Mo) для управления структурой, напряженным состоянием и механическими свойствами многоэлементного нитрида (TiAlSi)N. Осаждение слоев осуществлялось методом вакуумно-дугового испарения при разных потенциалах смещения на подложке Uₕ = -110 и -200 В. Установлено, что в бинанослойном композите мононитриды с большой энергией связи Me–N задают преимущественную ориентацию роста кристаллитов в тонких (нанометровых) слоях. При Uₕ = -110 В текстура роста формируется в композитах, содержащих мононитриды на основе переходных металлов с относительно небольшой атомной массой (Cr, Mo). В случае мононитрида на основе тяжелого металла (Zr) текстура образуется при большем Uₕ = -200 В. Наибольшая твердость достигается в текстурированных материалах, осажденных при Uₕ = -200 В. Это характерно как для монослойного многоэлементного нитрида (TiAlSi)N (достигнута твердость 42,5 ГПа), так и для многопериодных нанослойных композитов на его основе (наибольшая твердость 47,9 ГПа получена для композита (TiAlSi)N/ZrN).